2021
DOI: 10.1002/adma.202103150
|View full text |Cite
|
Sign up to set email alerts
|

Lithiation‐Enabled High‐Density Nitrogen Vacancies Electrocatalyze CO2 to C2 Products

Abstract: Electrochemical CO2 reduction to produce valuable C2 products is attractive but still suffers with relatively poor selectivity and stability at high current densities, mainly due to the low efficiency in the coupling of two *CO intermediates. Herein, it is demonstrated that high‐density nitrogen vacancies formed on cubic copper nitrite (Cu3Nx) feature as efficient electrocatalytic centers for CO–CO coupling to form the key OCCO* intermediate toward C2 products. Cu3Nx with different nitrogen densities are fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 47 publications
1
75
0
Order By: Relevance
“…Electrochemical reduction of carbon dioxide (CO 2 RR) toward high-valued product and closing the anthropogenic carbon cycle, powered by renewable electricity, has emerged as a competitive solution to achieve CO 2 resource re-utilization. [1][2][3][4] CO 2to-CO conversion has sparked tremendous attention, since CO…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical reduction of carbon dioxide (CO 2 RR) toward high-valued product and closing the anthropogenic carbon cycle, powered by renewable electricity, has emerged as a competitive solution to achieve CO 2 resource re-utilization. [1][2][3][4] CO 2to-CO conversion has sparked tremendous attention, since CO…”
Section: Introductionmentioning
confidence: 99%
“…The peak j CH 4 of 717 ± 33 mA cm −2 on the CuGaO 2 nanosheet catalyst represents the highest reported electrochemical CO 2 -to-CH 4 value to date (Figure 4e; Table S6, Supporting Information). [9][10][11][12][13]15,[29][30][31][32][33][34][35][36][37][38] S6, Supporting Information). f) Applied potentials (grey curve, left y-axis) and FE CH 4 (blue squares, right y-axis) versus time using the CuGaO 2 nanosheet catalyst at a constant total current density of -1 A cm −2 .…”
Section: Electrocatalytic Co 2 Reductionmentioning
confidence: 99%
“…In addition to doping, electrochemical ion insertion involving coupled ion–electron transfer is also an effective method to introduce alien elements into a host material for electronic or crystal structure modulation, and has been considered as a synthetic strategy to improve the catalytic performance of layer-structured materials 27 29 , such as LiCoO 2 for OER 30 and MoS 2 for HER 28 , where the Li concentration is an adjustable variable over a wide range 31 , 32 . Recently, Zheng’s group utilized a lithiation strategy to improve the CO 2 reduction performance of catalysts, including Cu 3 N x 33 and Sn 34 . Various studies have shown that RuO 2 can be inserted with Li ions for battery applications, and a solid solution phase forms before a Li:Ru = 1:1 ratio is reached 35 38 .…”
Section: Introductionmentioning
confidence: 99%